2002
DOI: 10.1111/j.0014-3820.2002.tb00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Speciation by Host Switch and Adaptive Radiation in a Fish Parasite Genus Gyrodactylus (Monogenea, Gyrodactylidae)

Abstract: Abstract. Four hundred Gyrodactylus species have been formally described, but the estimated number of species in this fish ectoparasite genus of Monogenean Platyhelminthes is more than 20,000. The unusually high species richness has lead to the hypotheses of speciation and adaptive radiation via host switching. These hypotheses were tested by reconstructing a molecular phylogeny for the subgenus G. (Limnonephrotus) which is a group of freshwater parasites, including five species infecting wild and farmed salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(90 citation statements)
references
References 32 publications
1
89
0
Order By: Relevance
“…Such a pattern has previously been noted in the monogeneans (Zietara & Lumme, 2002). This indicates that there is little coevolutionary pattern at the species level, and speciation takes place at the parasite-species/host-family level, coupled with longdistance postdispersal speciation.…”
Section: Speciation and Stasis Of Rhabdochona Speciessupporting
confidence: 65%
See 1 more Smart Citation
“…Such a pattern has previously been noted in the monogeneans (Zietara & Lumme, 2002). This indicates that there is little coevolutionary pattern at the species level, and speciation takes place at the parasite-species/host-family level, coupled with longdistance postdispersal speciation.…”
Section: Speciation and Stasis Of Rhabdochona Speciessupporting
confidence: 65%
“…This helps explain why not every freshwater fish has a Rhabdochona species, and why there are only 8000 species of Digenea, while there are more than 40, 000 species of potential vertebrate hosts to be infected (Hugot et al, 2001). A similar observation was inferred from gyrodactylid phylogenies (Simková et al, 2006;Zietara, & Lumme, 2002).…”
Section: Speciation and Stasis Of Rhabdochona Speciesmentioning
confidence: 59%
“…For example, Whittall & Hodges [47] found that changes to nectar spur length among different Aquilegia plant species were associated with shifts in specialist pollinators. Host switching is also thought to drive diversification among the estimated 20 000 species of Gyrodactylus fish ectoparasites [48].…”
Section: Discussionmentioning
confidence: 99%
“…teuchis is very close to the estimate of 5.5% suggested for the ITS region of the nuclear rDNA cluster of Gyrodactylus , an estimate derived from vicariance of G . aphyae on the Eurasian minnow ( Phoxinus phoxinus ) on opposite sides of the Baltic–White Sea watershed [15]. This seems surprising as mitochondrial DNA in animals generally evolves substantially faster than nuclear loci, but the variation among taxonomic groups is large, and for some basal groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, species of Gyrodactylus are capable of both sexual and asexual reproduction and new parasite populations may frequently originate from single founder individuals [14]. Given these unique reproductive features it is not surprising that host switching is believed to be the most abundant mode of speciation in Gyrodactylus [15]. Paradoxically, many Gyrodactylus species are highly host specific [12,16], a trait which is considered to result from the continuous adaptation inherent in a co-evolutionary arms race as first envisioned by Darwin [17].…”
Section: Introductionmentioning
confidence: 99%